Systematic Information Management in Quantum Computing: Progress and Challenges - Sood, Vaishali; Chauhan, Rishi Pal (IEEE transactions on engineering management, 2024)
Interdisciplinary research has a significant impact on invention. Quantum computing, a cutting-edge emerging technology in this area, has shown remarkable growth and development in the current time. Therefore, an inclusive analysis of the academic literature is needed to understand the research advancement in the domain. The present study fulfills the need by analyzing published academic work from the Scopus database using the CiteSpace visualization tool. The research findings classify the quantum domain into five stages for research exploration, viz. quantum state preparation, quantum entanglement, decoherence, quantum error correction, and quantum optimization. Keyword co-occurrence, document cocitation, and burst analysis of the network pinpoint nascent research topics, inclinations, and advancements in each stage. Inclusively, the systematized and comprehensive study presents an evolutionary pathway for future researchers to gain in-depth knowledge, identify essential research subjects, and identify challenging issues.